Clinical perspectives on the use of the GIP/GLP-1 receptor agonist tirzepatide for the treatment of type-2 diabetes and obesity - Gallwitz, Baptist (Frontiers in Endocrinology, 2022)
Incretin-based therapies with glucagon-like peptide-1 receptor agonists (GLP-1RA) are already established in the treatment of type 2 diabetes (T2D). The development of novel dual- or triple-receptor agonists that bind to the receptors not only for GLP-1 but also to the receptors for glucose-dependent insulinotropic polypeptide (GIP) and/or glucagon is intended to address different metabolic pathways for carbohydrate, lipid, and protein metabolism simultaneously. Dual- and triple-receptor agonists acting via different receptors and postreceptor pathways seem attractive in view of potentially additive or synergistic effects in the treatment of T2D and obesity. Recently, the first approval for a dual-receptor agonist marks an important step in this development. The GIP/GLP-1-receptor agonist tirzepatide was approved for the treatment of T2D by the Food and Drug Administration (FDA) in the USA for once-weekly subcutaneous injections in May 2022 and has just received a positive opinion from the European Medicines Agency (EMA). Tirzepatide dose-dependently leads to clinically significant reductions in glycemic parameters and body weight and has been shown to have stronger effects in reducing these parameters than standard antidiabetic therapy. This article summarizes the current clinical study program and the respective outcomes and highlights further potential indications for tirzepatide in the treatment of obesity and potentially other comorbidities of T2D.